Analisis Yuridis Implikasi Agreement On The Asean Harmonized Cosmetic Regulatory Scheme Terhadap Kebijakan Impor Kosmetik Di Indonesia (Kasus Kosmetik Merek Dnars) - Annisa, Ade Rizki; Jayakusuma, Zulfikar; Diana, Ledy (Peneliti.net, 2023)
Cosmetics trade is included in the free trade (ASEAN Free Trade Area) through harmonization of technical requirements, recognition of cosmetic registration approvals by adopting the ASEAN Cosmetic Directive (ACD). Online cosmetic notification is a new system for registering cosmetic products to representative bodies in each ASEAN country, which can be done anywhere and anytime online. However, in the case of imported cosmetics trade, there are still many who are caught by the Indonesian state BPOM who do not have cosmetic notifications and are also indicated to contain hazardous materials circulating in the Indonesian market. The problems discussed are about how implications of the Agreement on the ASEAN Harmonized Cosmetic Regulatory Scheme (AHCRS) on cosmetic import policies in Indonesia in the case of Dnars brand cosmetics and efforts to resolve trade cases of imported cosmetics containing dangerous and unnotified ingredients such as Dnars brand cosmetics. The analysis carried out is a qualitative analysis or research that is stated in writing.